Metode Tanya Jawab dan Penguatan Akidah Siswa SMP: Studi Kasus Pembelajaran Pendidikan Agama Islam - Nardi Widayat; Aang Mahyani (MAN 4 Kota Pekanbaru, 2026)
This study explores the implementation of the question-and-answer method and its contribution to strengthening akidah among junior high school students in Islamic Religious Education. Recent discussions on dialogic pedagogy emphasize that structured classroom dialogue and intentional questioning can foster deeper meaning-making and reflective reasoning. This research employed a qualitative case study design conducted in two Grade Eight classes at a junior high school in West Java. Data were collected through classroom observations across six learning sessions, semi-structured interviews with the teacher, focus group discussions with students, and analysis of instructional documents and student reflections. The data were analysed using reflexive thematic analysis involving familiarisation, coding, theme development, and interpretative synthesis. The findings reveal that the question-and-answer method contributed to the strengthening of students’ akidah through three interrelated mechanisms: dialogic openness for clarification, reasoning-based questioning that supports meaning construction, and corrective feedback that maintains doctrinal accuracy while encouraging participation. Observable developments included clearer articulation of the pillars of faith, more coherent reasoning when linking belief to daily decisions, and emerging reflective tendencies in written responses. The study concludes that dialogically structured questioning, when combined with supportive classroom climate and clear doctrinal anchoring, can serve as an effective pedagogical approach to fostering both conceptual understanding and reflective engagement in akidah education.